DETERMINANTS OF FARMERS’ PARTICIPATION IN FARM SETTLEMENT SCHEME IN LAGOS STATE, NIGERIA: LESSONS FOR FUTURE RURAL DEVELOPMENT PROGRAMME - Obayelu, Abiodun Elijah; Fabanwo, James Oladipupo (Journal of Agricultural Sciences (Belgrade), 2020)
In its determination to provide food and jobs for Nigerians, and appeal to educated young men to set the pattern for farming, many state governments have re-introduced Farm Settlement Scheme (FSS) / Graduate Employment Scheme once abandoned. One major challenge leading to programmes failure in Nigeria is the inability to know the influencing the factors to participations and constraints of such programmes. This study analysed the determinants of crop farmers’ participations in FSS in Lagos State with the aim of drawing some lessons for future rural development programme. One hundred and thirty (130) farmers were sampled through a two-stage sampling procedures. Data were collected with the aid of questionnaire and were analysed using both descriptive and inferential statistics such as the logit regression model. Results showed that about 67% of the respondents were male and 72% were married with mean farm size of 2.6ha (58%). The major constraining factors by farmers to participation in FSS were administrative bottlenecks, inadequate capital, and government interference. The logit regression showed that educational level farming experience, extension contacts and security of land under FSS were the significant variables (P<0.5) that directly influenced the probability of participation of the farmers in FSS in Lagos State, Nigeria. Farming experience is very crucial for the survival of FSS. Therefore, it is recommended that the determinants of participations and constraints to participation of the farmers be assessed in any rural development programme to know the necessary action to take to guide against failure. Effort at increasing extension contacts about FSS will further encourage farmers to participate in FSS.